PPP2CA Is a Novel Therapeutic Target in Neuroblastoma Cells That Can Be Activated by the SET Inhibitor OP449 - Galiger, Celimene; Dahlhaus, Meike; Vitek, Michael Peter; Debatin, Klaus-Michael; Beltinger, Christian (Frontiers in Oncology, 2022)
Neuroblastoma (NB) is the most common extracranial solid tumor in childhood and has a poor prognosis in high-risk cases, requiring novel therapies. Pathways that depend on phospho-signaling maintain the aggressiveness of NB. Protein phosphatase 2 (PP2A) with its catalytic subunit PPP2CA is a major phosphatase in cancer cells, including NB. We show that reduction of PPP2CA by knock-down decreased growth of NB cells and that complete ablation of PPP2CA by knock-out was not tolerated. Thus, NB cells are addicted to PPP2CA, an addiction augmented by MYCN activation. SET, a crucial endogenous inhibitor of PP2A, was overexpressed in poor-prognosis NB. The SET inhibitor OP449 effectively decreased viability of NB cells, independent of their molecular alterations and in line with a tumor suppressor function of PPP2CA. The contrasting concentration-dependent functions of PPP2C as an essential survival gene at low expression levels and a tumor suppressor at high levels are reminiscent of other genes showing this so-called Goldilocks phenomenon. PP2A reactivated by OP449 decreased activating phosphorylation of serine/threonine residues in the AKT pathway. Dasatinib, a kinase inhibitor used in relapsed/refractory NB, and OP449 synergized, decreasing activating AKT phosphorylations. In summary, concommitantly reactivating phosphatases and inhibiting kinases with a combination of OP449 and dasatinib is a promising novel therapeutic approach to NB.